2006
DOI: 10.1287/mnsc.1060.0553
|View full text |Cite
|
Sign up to set email alerts
|

Motivation, Governance, and the Viability of Hybrid Forms in Open Source Software Development

Abstract: Open source software projects rely on the voluntary efforts of thousands of software developers, yet we know little about why developers choose to participate in this collective development process. This paper inductively derives a framework for understanding participation from the perspective of the individual software developer based on data from two software communities with different governance structures. In both communities, a need for software-related improvements drives initial participation. The major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
428
1
8

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 709 publications
(450 citation statements)
references
References 37 publications
13
428
1
8
Order By: Relevance
“…This result firmly suggests that individuals with different perspectives on FOSS coalesce around FOSS projects, thus lending support to the findings of prior studies of FOSS developers' motivation, which have shown that FOSS projects are able to attract contributors with diverse motivations (Ghosh, 2005;Ghosh, et al, 2002;Hertel, et al, 2003;Lakhani and Wolf, 2005;Shah, 2006). In this respect, the dispersion of contributors' subjectivity across four discourses reflects the diversity of opinion characteristic of a community as heterogeneous as the FOSS community.…”
Section: Implications For Innovation Policy and Managementsupporting
confidence: 81%
“…This result firmly suggests that individuals with different perspectives on FOSS coalesce around FOSS projects, thus lending support to the findings of prior studies of FOSS developers' motivation, which have shown that FOSS projects are able to attract contributors with diverse motivations (Ghosh, 2005;Ghosh, et al, 2002;Hertel, et al, 2003;Lakhani and Wolf, 2005;Shah, 2006). In this respect, the dispersion of contributors' subjectivity across four discourses reflects the diversity of opinion characteristic of a community as heterogeneous as the FOSS community.…”
Section: Implications For Innovation Policy and Managementsupporting
confidence: 81%
“…Extensive research on why people contribute to open source projects has in short come to the following conclusions: motivations differ extensively between individuals (Juell- , the 'open' ideology fuels development (Shah, 2006), open source developers are both intrinsically (e.g. Ghosh, 1998) and extrinsically motivated (e.g.…”
Section: Ogd Usersmentioning
confidence: 99%
“…Ghosh, 1998) and extrinsically motivated (e.g. Kuan, 2001), participation is often driven by factors similar to other social movements (Hertel et al, 2003), and the motivations varies over time (Shah, 2006). In contrast, research on motivation among open data users is scarce.…”
Section: Ogd Usersmentioning
confidence: 99%
“…By fixing bugs and adding new features to the software, they benefit from their work themselves. Frequently, such an own-use motivation is the initial reason to start contributing to an open source project, but in the long run intrinsic motives such as fun and enjoyment become relevant (Shah 2006).…”
Section: Theory and Hypothesesmentioning
confidence: 99%